Effect of tembotrione herbicide on potato development - Dias, Roque Carvalho; Barbosa, Amanda Rocha; Miranda, Valesca Pinheiro; Melo, Christiane Augusta Diniz; Silva, Daniel Valadão; Reis, Marcelo Rodrigues (Revista de Ciências Agroveterinárias, 2018)
Tembotrione herbicide residues from maize crops in the soil can affect the growth of sensitive crops in succession, such as potatoes. In this sense, this study sought to evaluate the residual effect of tembotrione on growth and development of potato plants. A field experiment with randomized blocks design with four replications was conducted. The treatments were incorporated to the soil one day before the planting of the Atlantic potato cultivar and consisted of four doses of tembotrione: 8.4; 16.8; 33.6 and 50.4 g ha-1; representing 8.4; 16.8; 33.6 and 50.0% of the recommended dose for maize, and a control treatment (without herbicide and weeding). Fresh matter mass of tuber (FMMT), number of stems (NS), number of tubers (NT) per plant and total dry matter mass (aerial parts and stem) (DMM) were evaluated at 60 and 90 days. FMMT, NT and DMM decreased with increasing doses of tembotrione. The largest reductions on both evaluated seasons were found for the 50.4 g ha-1 i.a. dose. The number of stems was not influenced by the tembotrione herbicide doses regardless of evaluated season. The results indicated that the presence of tembotrione in soil reduced growth and the number of tubers produced by potato plants.